Altered proportions of circulating CXCR5+ helper T cells do not dampen influenza vaccine responses in children with rheumatic disease. Issue 28 (19th June 2019) - Laestadius, Åsa; Ingelman-Sundberg, Hanna M.; Myrberg, Ida Hed; Verme, Anna; Sundberg, Erik; Schweiger, Brunhilde; Saghafian-Hedengren, Shanie; Nilsson, Anna
Abstract: Biological therapy options for the treatment of rheumatic disease target molecules that can affect the cross-talk between innate and adaptive immune responses upon vaccination. Influenza vaccination in children with rheumatic disease has been recommended, but there are only sparse data on the quality of vaccine responses from pediatric patients treated with biological therapy. We conducted an influenza vaccine study over 3 consecutive seasons where the antibody response to TIV was evaluated in children with PRD (n = 78), including both non-treated (n = 17) and treated (with methotrexate, TNF-inhibitors with or without methotrexate, or IL-inhibitors, n = 61) children as well as healthy age-matched controls (n = 24). Peripheral B cells, T and NK cell populations, as well as CXCR5+ (follicular) helper T cells (TFH ) and chemokines involved in antibody responses were assessed prior to immunization in the same cohort. Data on disease duration, therapy and data on previous influenza vaccinations were retrieved. The proportion of circulating TFH cells were significantly lower in non-treated children with PRD compared to treated patients and healthy controls. The significantly lower proportion of TFH cells was mirrored by a marked significant increase in CXCL13 serum level, the ligand for CXCR5, with higher levels in non-treated children with PRD compared to treated patients and healthy controls. However, the proportion of TFH cells or CXCL13 level at the time of vaccination was not a predictor of the antibody response to TIV in this cohort of children. Children with PRD had an overall similar response to TIV as healthy children. Although not significant, children treated with TNF-inhibitors differed as a few children remained seronegative towards H3N2- and influenza B viruses after immunization. Our data show that children with PRD respond to TIV as healthy children. Furthermore, plasma CXCL13 levels did not correlate to the proportion of TFH cells in blood prior to immunisation, or to antibody responses following immunization.